Pengaruh Jumlah Wajib Retribusi IMB Pendapatan Perkapita dan Jumlah Pengawas IMB terhadap Penerimaan Retribusi Izin Mendirikan Bangunan (IMB) Kota Samarinda - Taufik Hur Rahman; Aji Sofyan Effendi; Erwin Kurniawan (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this study was to determine the effect Payers IMB retributions, income of Per Capita, and supervisory of IMB Total Revenue Retribution in Samarinda by using a model of Multiple Linear Regression analysis tool used SPSS version 20. This study uses secondary data, from 2005-2014 Payers IMB Retribution , the data Per capita income. Number of Supervisors IMB The data obtained from Dinas Cipta Karya dan Tata Kota Samarinda (CIPTAKOT),Badan Pelayanan Perizinan Terpadu Satu Pintu (BPPTSP), Badan Pusat Statistik(BPS) and Dinas Pendapatan Daerah (DISPENDA). Samarinda City. From the results of this study note that partially that Retributions Payers IMBinfluence the IMB Retribution Revenue, income of Per Capita influence the IMB Retribution Revenue, Total Supervisory IMB does not affect the IMB Retribution Revenue.Keywords: IMB Retributions